LAPORAN KASUS HIPERTIROIDISME PADA KEHAMILAN: HASIL IBU DAN NEONATAL - Afifah Muthmainnah; Ruza P Rustam (JOMIS (Journal of Midwifery Science), 2024)
Normal pregnancy induces some clinical findings similar to thyroxine excess; Clinically mild thyrotoxicosis may be difficult to diagnose. Hyperthyroidism in pregnancy is a hyperthyroid condition that existed before pregnancy, or a condition that was acquired during pregnancy. The aim of this study is to determine the management of hyperthyroidism in uncontrolled hyperthyroid pregnancies and the clinical outcomes for mothers and neonates. The location of the research was Arifin Achmad Rekanbaru Regional Hospital. The research method is a study that explores a problem in detail, and collects in-depth data and includes various sources of information that will help doctors gain insight into hyperthyroidism in pregnancy. Data was taken retrospectively from medical records, from February to April 2021. The results of the study were that the management of hyperthyroidism in the first and second patients was the same, but the maternal and neonatal outcomes obtained were different. In both cases, both experienced uncontrolled hyperthyroidism. The neonatal outcome of the first patient was poor, but the mother survived. Unlike the second patient who died of thyroid storm, the baby was saved. Treatment should be carried out in intensive care areas that include special care units during labor and delivery units. Patients with uncontrolled hyperthyroidism are in the high risk group and require early fetal surveillance examination. Treatment with propylthiouracil, a thionamide that inhibits thyroid biosynthesis and peripheral conversion of T4 to T3 has become the drug of choice for hyperthyroidism in pregnancy. Proper management of hyperthyroidism during pregnancy is very important for the mother and fetus. Untreated hyperthyroidism can lead to pregnancy-related complications such as premature birth, growth restriction, and even fetal death.